GAMBARAN POLA MAKAN, AKTIFITAS FISIK DAN STATUS GIZI PADA KARYAWAN UD ALFA STAR BUSANA DAN PLS ERVINA MEDAN TAHUN 2012 - Aklima Zahra M; Evawany Y Aritonang; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
The increasing of income level of the productice age group such as employees, so that there is an increasing in labor force in urban areas causes a change in lifestyle. The change in lifestyle includes eating patterns, physical activities and nutritional status. The eating patterns in large cities have been changing from traditional diet to modern diet and the type of activity that does not expend energy has negative impact on health and nutrition issues.This is a descriptive study with cross-sectional research design. The population is all employees at Business Trade Alfa Star Clothing and PLS Ervina with a total of 100 people, sampling conducted by a total sampling. Data collected through interviews using questionnaires, food frequency forms, food recall forms and physical activity forms.The result showed that the eating patterns of tailor employees at Business Trade Alfa Star Clothing and PLS Ervina in unfavorable category as much as 72% with the type and frequency of eating on average rarely (1-2x/week). The average of energy consumed sufficiently as much as 46% and protein is lower 62%. The most physical activity in medium category is 84%. Nutritional status based on BMI largely on the normal category as much as 50% and 39% for the fat one.The need for attention of the company and employees to be able to consume a complete diet (balanced), especially vegetables and fruits every day. Physical activity such as sports and activities that expend energy in order to be healthy and fit every day. Keywords:  eating pattern, physical activity, nutritional status, employees tailor.